Cooling water intake system safety analysis based on impingement probability - Fu, Xiaocheng; Du, Fenglei; Huang, Xiaodong; Pei, Juan; Zhang, Zhenglou; Xing, Xiaofeng; Pu, Xiang (Frontiers in Marine Science, 2023)
Invasion or aggregation of marine organisms in cooling water intake systems (CWIS) has gradually become an important problem affecting the safety of nuclear power plants with environmental and climate changes. In this study, a 3-dimensional numerical model (TELEMAC-3D) was used to determine the impingement probability in a typical nuclear power plant with a once-through cooling system, and the effect on CWIS safety. The factors controlling impingement probability were also analyzed. Results show that (1) impingement probability decreased rapidly with an increase in distance from the CWIS. In addition, the distance of the impingement effect of a nuclear power plant with six units was mainly within 1 km of the CWIS. (2) Impingement probability increased with water withdrawal, and as distance to the CWIS increased, the increase in probability increased. (3) Generally, an increase in tide strength led to a decrease impingement probability. (4) Near the CWIS, the impingement probabilities of areas upstream or downstream of the CWIS along the tidal flow direction were much higher than those not in those areas. (5) An increase in water depth significantly reduced impingement probability. When the water depth of the CWIS increased from 5 m to 15 m, impingement probability was reduced up to 30%. Based on the above findings, the following suggestions were made to minimize the impingement effects on CWIS safety: first, the CWIS of coastal nuclear power plants should be set in an area with low aquatic biomass, strong tides, deep water, and few surface species within the range of 1 km, and second, the amount of cooling water withdrawal or velocity should be reduced as much as possible.